DOMESTIFIKASI PEREMPUAN SAMIN DALAM KHASANAH MASYARAKAT ISLAM MODERN - Mukodi Mukodi; Afid Burhanuddin (AL-TAHRIR, 2015)
Abstract: The dominance is a term that is owned by a variety of entities ranging from the lowest social strata up to those who have the highest power in public domain, even in the global public organization. The domination of the lowest domain up to the highest one can be transformed into a variety of issues including the role of someone in the public domain. Problems will arise when the role of men are much more dominant than women as shown in Samin community in Blora. Based on  the concept of gender, this study tried to dismantle and explore the myths of Samin  community and the commodity of Saminisme in Blora. The women of  Samin were still placed as a sub-ordinate of  men, that is, the Samin community in the village of Kelopo Dhuwur, called Wong Sikep (people of Sikep); Wong Samin who, in a particular level, still showed strong patriarchal culture in daily life, especially the issue of the concept of matchmaking in marriage and marriage itself. This condition was as a result of low level of their education which led to weakness of involvement of Samin women in public spaces. The local culture of this community had constructed domestication of women. Samin women's empowerment efforts had been done in two ways by its stakeholders, namely, Samin myth demolition and removal Saminisme commodities. The success and the positive effect of these two efforts had reached their attainment, although the results still  showed  the minimum  ideal outcome.الملخص :إن موضوع "الهيمنة" أصبح لشتى الجهات من المجتمعات، من الجهة الإجتماعية السفلى إلى ولاية السلطة العليا بل وفي المنظمات العالمية. ظهرت هذه الهيمنة – من المستوى السافل إلى العالي – في شتّى الأشياء ومنها دور المرء في المجتمع. نشأت المشكلة إذا كانت هيمنة الرجل على المرأة أشد بالنسبة للمرأة، كما وقع هذا في المجتمع "سامين" بلورا. حاولت هذه الدراسة – بالمنظور الجنسي- كشف وعرض ودراسة أسطورة مجتمع "سامين" وبضاعة "السامينية" في بلورا. -كانت المرأة في المجتمع "سامين " إلى الآن تحت هيمنة الرجل . أظهر المجتمع الساميني في – جوانب خاصة – قوة ثقافة الهيمنة في حياتهم اليومية، خاصة في اختيار الزوجة والنكاح. وقع هذا بسبب قلتهم الحصول على التربية وأدى إلى ضعف دور المرأة السامينية في المجتمع. صوّرت الثقافة المحلية لهذا المجتمع " أن المرأة ربّة البيت". توالت المحاولات من الجهات المعنية لترقية النساء السامينيات عن طريقتين، 1) نسف وإزالة أسطورة "السامين"، 2) وإزالة بضائعية السامين. نجحت هذه المحاولات إلى حدّ ما، لكن لم يكن مقنعا للجميع.Abstrak: Dominasi merupakan terma yang dimiliki oleh beragam entitas dari mulai ranah sosial terendah sampai pada wilayah kekuasaan tertinggi, bahkan dalam ranah oraganisasi global. Dominasi dari ranah terendah sampai tertinggi ini dapat menjelma dalam beragam hal termasuk peran seseorang dalam ranah publik. Problem akan muncul ketika dominasi peranan kaum laki-laki begitu kontras dibandingkan kaum perempuan sebagaimana nampak dalam masyarakat Samin di Blora. Melalui konsep gender kajian ini mencoba untuk membongkar dan megeksplorasi mitos masyarakat Samin dan komoditi Saminisme di Blora. Kaum perempun Samin hingga kini masih ditempatkan sebagai sub-ordinat laki-laki. komunitas Samin di Desa Kelopo Dhuwur, yang disebut dengan Wong Sikep, Wong Samin dalam tataran tertentu masih menampilkan kuatnya budaya patriarki dalam kehidupan keseharian khususnya persoalan perjodohan dan  perkawinan. Kondisi ini akibat dari rendahnya tingkat pendidikan yang memicu lemahnya keterlibatan perempuan Samin di ruang publik. Budaya lokal komunitas ini mengkonstruksikan domestikasi perempuan. Upaya pemberdayaan perempuan Samin oleh para pemangku kepentingan masih tetap dilakukan melalui dua cara, yakni pembongkaran mitos Samin, dan penghilangan komiditi Saminisme. Keberhasilan dan efek positif dari dua upaya ini telah terbukti, walaupun belum menunjukkan capaian yang ideal.Keywords: domestifikasi perempuan, Samin Surosentiko, Blora, Islam modern.